Stable Hydrogen Isotope Fractionations during Autotrophic and Mixotrophic Growth of Microalgae - Estep, Marilyn F. (Plant Physiol, 1981)
Isotope effects, studied with precision isotope ratio mass spectrometry, have been used to locate critical steps in the H metabolism of plants. By manipulating the growth conditions of versatile microalgae, the discrimination of H isotopes between water in the growth medium and the organically bonded H in carbohydrates from these microalgae was −100 to −120‰ and was regulated by both the light and the dark reactions of photosynthesis. Photosynthetic electron transport discriminated against the heavy isotope of H and formed a pool of reductant available for biosynthesis that was enriched in the light isotope. Growth in red or white light activated phosphoglyceric acid reduction and H isotope discrimination, when H was fixed into organic matter. An additional fractionation of −30 to −60‰ occurred during the biosynthesis of proteins and lipids and was associated with glycolysis. This fractionation paralleled the isotope effect seen in carbohydrate metabolism, indicating that H metabolism in photosynthesis was coupled with that in dark biosynthetic reactions via the pool of reductant, probably NADPH.